Analysis and Diminution of NoSQL Injection attacks - Patil, Pritesh; Gaikwad, Ashwini; Badekar, Rachana; Urade, Ankita; Hirve, Rutuja (IJRDO -Journal of Computer Science Engineering, 2017)
Scalability and ease of use has been one of the major reasons behind the popularity of NoSQL storage systems. Flexibility and scalability of NoSQL databases are major cause for adoption and popularity. Unfortunately, they lack the security measures and awareness that are required for data protection. The global exposure of these applications makes them prone to the attacks because of presence of vulnerabilities. These security vulnerabilities continue to infect the web applications through injection attacks thus enabling the attackers to attack on the database by injecting malicious code into the statements passed to the database because the new data models and query formats of NoSQL data which in turn makes the attack divergent.